Repositioning of the Caribbean in the new global economic order. - ARTHUR, Owen (1996)
Points out that in the course of this decade and in short order, the Caribbean Community will have to make critical choices, both in respect of its own options for its economic development, and in respect of its relationship to the new global economy and the evolving regional blocs. Evaluates the dimensions of the changes set in train by the restructuring of global economic relationships, their implications for the Caribbean Community, and reflects on what can and must be done to effectively reposition the Caribbean in the new global order.